Chemical and Structural Information from the Enamel of a Troodon Tooth Leading to an Understanding of Diet and Environment. Issue 11 (November 2016) - Feng, Renfei; Maley, Jason M.; Schatte, Gabriele; Hoffmeyer, Ruth E.; Brink, Kirstin S.; Ellis, Thomas; Brinkman, Don; Sammynaiken, Ramaswami
Synchrotron micro X-ray fluorescence (XRF) spectroscopy with two-dimensional element mapping, micro X-ray diffraction (XRD), electron spin resonance spectroscopy (ESR) and atomic force microscopy (AFM) were used to investigate the chemical and structural nature of the enamel of a tooth from Troodon, a small theropod dinosaur. These methods show that the crystallites in the Troodon tooth are submicron-sized carbonated calcium hydroxyapatite, which are semi-randomly oriented with a preferred orientation of (002) towards the surface of the tooth. Transition metal ions are distributed in the voids between crystallite clusters. Comparison of the ESR spectra indicates that the Troodon tooth had less exposure to UV than a fossilized crocodile tooth.